Problems of Teaching English at Intermediate Stage Public Schools in Iraq from the Perspective of English Language Teachers: Solutions and Suggestions (مجلة ديالى للبحوث الانسانية, 2023)
The current study aimed to investigate the problems of teaching English in Iraqi public schools for the intermediate stage in   Baghdad city from the perspective of English language teachers. In other words, this study attempted to determine the reasons behind the failure of teaching of English language and to identify the most important treatments and suggestions for these problems. A selective sample of 50 teachers was purposefully chosen by the researcher to complete the questionnaire in order to achieve the objectives of the study in Al-Ajyal Intermediate School in Baghdad during the second semester of the academic year 2021/2022. Those teachers represent a variety of age groups, genders, educational backgrounds, and teaching experiences. Open interviews and questionnaire were used as data collection methods. The results indicated that there are many problems in teaching English in the public schools of Baghdad. These problems can be divided into two groups: First, problems related to the teachers themselves in terms of knowledge, experience, and attitudes, such as the need for training teachers repeatedly and the misuse of the mother language (Arabic) as a medium of instruction. Second, the problems related to the teaching and learning environment (the unsafe environment resulting from the unsafe situation in Iraq) and resources (libraries, teaching aids, supporting materials, and audio-visual teaching equipment) that are not available in public schools. Respondents suggested some ways and solutions to deal with these problems, for example, offering pre-service and in-service training programs for English language teachers. The study suggested some fruitful suggestions. Recommendations are provided at the end of the study